3D X-ray imaging methods in support catheter ablations of cardiac arrhythmias - Stárek, Zdeněk; Lehar, František; Jež, Jiří; Wolf, Jiří; Novák, Miroslav (The international journal of cardiovascular imaging, 2014)
Cardiac arrhythmias are a very frequent illness. Pharmacotherapy is not very effective in persistent arrhythmias and brings along a number of risks. Catheter ablation has became an effective and curative treatment method over the past 20 years. To support complex arrhythmia ablations, the 3D X-ray cardiac cavities imaging is used, most frequently the 3D reconstruction of CT images. The 3D cardiac rotational angiography (3DRA) represents a modern method enabling to create CT like 3D images on a standard X-ray machine equipped with special software. Its advantage lies in the possibility to obtain images during the procedure, decreased radiation dose and reduction of amount of the contrast agent. The left atrium model is the one most frequently used for complex atrial arrhythmia ablations, particularly for atrial fibrillation. CT data allow for creation and segmentation of 3D models of all cardiac cavities. Recently, a research has been made proving the use of 3DRA to create 3D models of other cardiac (right ventricle, left ventricle, aorta) and non-cardiac structures (oesophagus). They can be used during catheter ablation of complex arrhythmias to improve orientation during the construction of 3D electroanatomic maps, directly fused with 3D electroanatomic systems and/or fused with fluoroscopy. An intensive development in the 3D model creation and use has taken place over the past years and they became routinely used during catheter ablations of arrhythmias, mainly atrial fibrillation ablation procedures. Further development may be anticipated in the future in both the creation and use of these models.
Keywords: Imaging, Three-Dimensional; Software; software; Humans; Multidetector Computed Tomography; Heart Conduction System; Predictive Value of Tests; chirurgie s pomocí počítače; akční potenciály; převodní systém srdeční; lidé; Radiography, Interventional; zvířata; Action Potentials; katetrizační ablace; multidetektorová počítačová tomografie; koronární angiografie; Surgery, Computer-Assisted; prediktivní hodnota testů; srdeční arytmie; Radiographic Image Interpretation, Computer-Assisted; Coronary Angiography; zobrazování trojrozměrné; rentgenový obraz - interpretace počítačová; Arrhythmias, Cardiac; Animals; intervenční radiografie; Catheter Ablation